Analisis Gaya Belajar Siswa melalui Media Pembelajaran Daring di Masa Pandemi Covid-19 - Khabiburrokhman, Khabiburrokhman; Khamid, Abdul; Ali, Yusuf Faisal (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2020)
Covid-19 is a highly contagious virus and spreads very quickly throughout the world. This has a broad impact on all segments of social life, including education. Responding to this, the Indonesian government temporarily eliminates the teaching and learning process in schools and conducts learning from home. Educators are required to be able to provide instruction to students in accordance with this situation and condition faced. Therefore, it is important for teachers to understand the learning styles of their students as an orientation for determining appropriate learning media. This study explores the learning styles of students at Madrasah Aliyah Negeri 1 Semarang and discovers the most suitable learning media in accordance with the students’ learning styles. The results showed that visual learning style was the most preferred so instructional videos were found as the most appropriate teaching media. Keywords: Learning Style, Learning Media, Online Learning